2003
DOI: 10.1044/1092-4388(2003/063)
|View full text |Cite
|
Sign up to set email alerts
|

Relevance and Speed of Message Delivery Trade-Offs in Augmentative and Alternative Communication

Abstract: This report is the first in a series of investigations designed to test a theory identifying the effects of conversational trade-offs between selected maxims on public attitudes toward augmentative and alternative communication (AAC) system users and their communication. In the current study, the trade-offs between the relevance of a prestored message and its speed of delivery were examined. Participating were 96 sales clerks. Twelve scripted videotaped conversational conditions, involving an AAC customer and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
3
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 10 publications
2
31
3
2
Order By: Relevance
“…Finally, this study provided another opportunity to investigate whether or not gender of either the person rating or the person using AAC has an effect on the attitudes measured. While our previous studies have found no such effect (Bedrosian et al, 2003;Hoag et al, 2004), these results have been contrary to those reported in other investigations regarding more positive attitudes of females versus males toward people with disabilities (e.g., Beck, Bock, Thompson, & Kosuwan, 2002;Blockberger, Armstrong, O'Connor, & Freeman, 1993).…”
Section: Introductioncontrasting
confidence: 82%
See 3 more Smart Citations
“…Finally, this study provided another opportunity to investigate whether or not gender of either the person rating or the person using AAC has an effect on the attitudes measured. While our previous studies have found no such effect (Bedrosian et al, 2003;Hoag et al, 2004), these results have been contrary to those reported in other investigations regarding more positive attitudes of females versus males toward people with disabilities (e.g., Beck, Bock, Thompson, & Kosuwan, 2002;Blockberger, Armstrong, O'Connor, & Freeman, 1993).…”
Section: Introductioncontrasting
confidence: 82%
“…At first glance, it may appear that brevity is more important than speed, since in the previous investigations (Bedrosian et al, 2003;Hoag et al, 2004), the edited and thus slowly delivered messages were preferred over the quickly delivered messages containing partly relevant or an inadequate amount of information. Given the overall value placed on speed of message delivery (Higginbotham & Wilkins, 1999), however, and the likely reduced interference of repeated words with information exchange, it is possible that a quickly delivered, prestored message containing repetitive words will be preferred over an edited, and therefore, slowly delivered message without them.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Furthermore, the generativity of digitized messages is constrained to whatever is prerecorded, unlike synthesized speech in which new messages can be generated directly [see , for a clear discussion of these issues]. Bedrosian et al [2003] and Hoag et al [2004] have recently documented some of the functional repercussions of messages whose content is not quite accurate on the process of communication. Scripted scenarios were videotaped of AAC users as they attempted to purchase a book in a bookstore.…”
Section: Voice Outputmentioning
confidence: 99%